Mobilização popular na mídia: uma análise crítica do discurso da imprensa recifense sobre o Movimento Ocupe Estelita. - Nascimento , Anamaria Melo do (2019)
This research aims to critically analyze the discourses of printed media in Pernambuco on the Ocupe Estelita Movement, an organized civil society manifestation opposed to the construction of the real estate project named Novo Recife, of the Novo Recife Consortium, for Cais José Estelita Cais, central Recife. This study also situates the Occupy Estelita Movement in the historical and social context of Pernambuco, since the historical conjuncture of the analyzed phenomenon is fundamental for the Critical Discourse Analysis (CDA), an interdisciplinary approach to the study of discourse that views language as a form of social practice. The analyzed articles were published between February 29th, 2012 and November 17th, 2017 in the Jornal do Commercio and Folha de Pernambuco. This study was guided by the analysis model proposed by Norman Fairclough in Discourse and Social Change (2001). From the three-dimensional model elaborated by the linguist, it was possible to analyze the media discourse in relation to the text, discursive practice and social practice. In the textual dimension of the analysis, the vocabulary was considered. Within the scope of discursive practice, the textual analysis was related to the aspects that define production, distribution, consumption, context and intertextuality. The issues related to ideology and hegemony, which refers to social practice, was also analyzed. These dimensions were not analyzed in isolation, but together, in a dialectical approach. The theoretical-conceptual basis of the research also articulates concepts of Critical Discourse Analysis in other authors, such as van Dijk (1988, 1996, 2002, 2015), Pedro (1997) and Resende and Ramalho (2004, 2014). Also useful were contributions by authors of French line discourse analysis, such as Charaudeau (2013) and Maingueneau (2005). The historical context of the Occupy Estelita Movement was understood from authors such as Lefebvre (2001), Harvey (2012), Santos (1993) and Zizek (2012). The contributions of authors as Silverstone (2002), Thompson (2009) and Lage (2001; 2005) were used to understand the characteristics and formation of the media discourse. It was noticed, in most of the analyzed articles, that the discourse of Jornal do Commercio and Folha de Pernambuco was favorable to the construction of the Novo Recife project and, therefore, contrary to the Ocupe Estelita Movement.